Complement C3a and C5a receptor blockade modulates regulatory T cell conversion in head and neck cancer. Issue 3 (31st March 2021) - Gadwa, Jacob; Bickett, Thomas E; Darragh, Laurel B; Knitz, Michael William; Bhatia, Shilpa; Piper, Miles; Van Court, Benjamin; Bhuvane, Shiv; Nguyen, Diemmy; Nangia, Varuna; Kleczko, Emily K; Nemenoff, Raphael A; et al.
Abstract : Background: Resistance to therapy is a major problem in treating head and neck squamous cell carcinomas (HNSCC). Complement system inhibition has been shown to reduce tumor growth, metastasis, and therapeutic resistance in other tumor models, but has yet to be explored in the context of HNSCC. Here, we tested the effects of complement inhibition and its therapeutic potential in HNSCC. Methods: We conducted our studies using two Human Papilloma Virus (HPV)-negative HNSCC orthotopic mouse models. Complement C3aR and C5aR1 receptor antagonists were paired with radiation therapy (RT). Tumor growth was measured and immune populations from tumor, lymph node, and peripheral blood were compared among various treatment groups. Genetically engineered mouse models DEREG and C3-/- were used in addition to standard wild type models. Flow cytometry, clinical gene sets, and in vitro assays were used to evaluate the role complement receptor blockade has on the immunological makeup of the tumor microenvironment. Results: In contrast to established literature, inhibition of complement C3a and C5a signaling using receptor antagonists accelerated tumor growth in multiple HNSCC cell lines and corresponded with increased frequency of regulatory T cell (Treg) populations. Local C3a and C5a signaling has importance for CD4 T cell homeostasis and eventual development into effector phenotypes. Interruption of this signaling axis drives a phenotypic conversion of CD4 + T cells into Tregs, characterized by enhanced expression of Foxp3. Depletion of Tregs reversed tumor growth, and combination of Treg depletion and C3a and C5a receptor inhibition decreased tumor growth below that of the control groups. Complete knockout of C3 does not harbor the expected effect on tumor growth, indicating a still undetermined compensatory mechanism. Dexamethasone is frequently prescribed to patients undergoing RT and inhibits complement activation. We report no deleterious effects associated with dexamethasone due to complement inhibition. Conclusions: Our data establish Tregs as a pro-tumorigenic driver during complement inhibition and provide evidence that targeted C3a and C5a receptor inhibition may add therapeutic advantage when coupled with anti-Treg therapy.